PENGARUH PENAMBAHAN STYRENE BUTADIENE RUBBER (LATEX)TERHADAP BETON MUTU TINGGI DENGAN FILLER FLY ASH (Tinjaun Terhadap Kuat Tekan,Modulus Elastisitas dan Permeabilitas) - Ambar Susanto (Universitas Batanghari Jambi, 2011)
The addition of styrene butadiene rubber (latex) on high strength concrete with fly ash filler obtained results of compressive strength of concrete at 28 days fc '= 60.35 MPa with the pattern of failure are cones and shear type. In addition, the resulting modulus of elasticity (E) = 26661.71 MPa and Poisson's ratio (n) 0.2241. Permeability test results on high strength concrete with fly ash filler added some styrene butadiene rubber (latex) get the value of permeability coefficient (k) = 1.111E-08 m / sec and at 0767 cm penetration.